Labor Position and Its Impact on The Birth Process: A Literature Review - Ahmar, Hamdiah; Sofyana , Sherllia; Suciati , Siti; Ernawati, Ernawati; Liantanty , Firda (Journal of Current Health Sciences, 2025)
Variations in labor positions can enhance childbirth by improving maternal comfort, satisfaction, and reducing complications like prolonged labor and perineal trauma. This review aimed to evaluate the impact of labor positions on specific outcomes: duration of labor, perineal integrity, maternal comfort, and medical intervention rates. A systematic literature search was conducted in April 2025 using PubMed, SpringerLink, and ScienceDirect databases, employing keywords such as "birthing position," "maternal outcomes," and "alternative position during labor." Inclusion criteria were quantitative studies, systematic reviews, and international guidelines; opinion articles, editorials, and case reports were excluded. The PRISMA approach identified 13 studies from an initial 58 records, assessed using the GRADE criteria. Results indicated upright positions (standing, squatting, sitting, kneeling) utilize gravity to significantly shorten the second labor stage, widen pelvic diameter, and reduce medical interventions like cesarean sections. Squatting and kneeling specifically facilitated faster fetal expulsion, whereas lateral positions improved perineal integrity and minimized trauma. This review recommends healthcare facilities adopt flexible labor position policies and highlights the importance of longitudinal and population-based research to further assess the long-term maternal and neonatal impacts of implementing these alternative labor positions.